Factors underlying masking release by voice-gender differences and spatial separation cues in multi-talker listening environments in listeners with and without hearing loss - Oh, Yonghee; Hartling, Curtis L.; Srinivasan, Nirmal Kumar; Diedesch, Anna C.; Gallun, Frederick J.; Reiss, Lina A. J. (Frontiers in Neuroscience, 2022)
Voice-gender differences and spatial separation are important cues for auditory object segregation. The goal of this study was to investigate the relationship of voice-gender difference benefit to the breadth of binaural pitch fusion, the perceptual integration of dichotic stimuli that evoke different pitches across ears, and the relationship of spatial separation benefit to localization acuity, the ability to identify the direction of a sound source. Twelve bilateral hearing aid (HA) users (age from 30 to 75 years) and eleven normal hearing (NH) listeners (age from 36 to 67 years) were tested in the following three experiments. First, speech-on-speech masking performance was measured as the threshold target-to-masker ratio (TMR) needed to understand a target talker in the presence of either same- or different-gender masker talkers. These target-masker gender combinations were tested with two spatial configurations (maskers co-located or 60° symmetrically spatially separated from the target) in both monaural and binaural listening conditions. Second, binaural pitch fusion range measurements were conducted using harmonic tone complexes around a 200-Hz fundamental frequency. Third, absolute localization acuity was measured using broadband (125–8000 Hz) noise and one-third octave noise bands centered at 500 and 3000 Hz. Voice-gender differences between target and maskers improved TMR thresholds for both listener groups in the binaural condition as well as both monaural (left ear and right ear) conditions, with greater benefit in co-located than spatially separated conditions. Voice-gender difference benefit was correlated with the breadth of binaural pitch fusion in the binaural condition, but not the monaural conditions, ruling out a role of monaural abilities in the relationship between binaural fusion and voice-gender difference benefits. Spatial separation benefit was not significantly correlated with absolute localization acuity. In addition, greater spatial separation benefit was observed in NH listeners than in bilateral HA users, indicating a decreased ability of HA users to benefit from spatial release from masking (SRM). These findings suggest that sharp binaural pitch fusion may be important for maximal speech perception in multi-talker environments for both NH listeners and bilateral HA users.